Case-Based Plan Recognition in Computer Games - Fagan, Michael; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2003)
In this paper we explore the use of case-based plan recognition to predict a player?s actions in a computer game. The game we work with is the classic Space Invaders game and we show that case-based plan recognition can produce good prediction accuracy in real-time, working with a fairly simple game representation. Our evaluation suggests that a personalized plan library will produce better prediction accuracy but, for Space Invaders, good accuracy can be produced using a plan library derived from the game play of another player.
Keywords: Computer Science